The Kinetic Analysis and Adsorption Isotherm of Chicken Egg Shells and Membranes Against Synthetic Dyes - Hevira, Linda; Gampito (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2022)
Textile industry waste at this time is enough to worry the community and the environment. The presence of synthetic dyes in water is hazardous, even in small concentrations. These synthetic dyes are derivatives of aromatic compounds such as benzene, toluene, and naphthalene, which are more resistant and stable than natural dyes. The adsorption method is used because it is easier to do, has no side effects, and does not require complicated and expensive equipment. In this study, the shells and membranes of discarded chicken eggs became useful as an absorbent of indigo carmine dye with an adsorption capacity of 6.399 mg/g. The adsorption reaction kinetics were analyzed from the optimal contact time data, and the reaction isotherm was analyzed from the adsorption optimal concentration data. The kinetic model that fits the research is the second pseudo-order with R2 = 0.9998. The adsorption mechanism demonstrates that the adsorption capacity is proportional to the adsorbent's active sites. The adsorption isotherm model, with R2 = 0.9748, is more closely related to the Freundlich isotherm model, indicating that adsorption occurs in several layers. From an economic point of view, chicken egg shells and membranes can be recommended as dye absorbers that are eco-friendly, efficient, and simple to obtain while lowering organic solid waste.